Zebrafish embryotoxicity and teratogenic effects of Christia vespertilionis leaf extract - Norazhar, Anis Irfan; Wan Ibrahim, Wan Norhamidah; Saleh Hodin, Nur Atikah; Mohd Faudzi, Siti Munirah; Shaari, Khozirah (Universiti Putra Malaysia Press, 2022)
Christia vespertilionis or butterfly wings is a traditional medicinal plant used to treat, among others, colds and bronchitis. The plant was also reported to be a remedy for cancer, with several products based on the plant becoming commercially available, raising some safety concerns on its consumption. The present study was carried out to assess the toxic and teratogenic effects of the plant on the embryonic development of zebrafish (Danio rerio) as the animal model. Zebrafish embryos were exposed to 50, 100, 200, 400, and 800 μg/mL of the methanolic leaf extract of C. vespertilionis, starting from 5 to 120 hours post-fertilization (hpf). The median lethal concentration (LC50) value of the extract was determined to be 419.84 μg/mL, which is within the safety limit stipulated by the Organisation for Economic Co-operation and Development (OECD) guideline. However, results from the teratogenicity evaluation revealed multiple signs of developmental defects in embryos exposed to 200 μg/ mL and higher concentrations of the extract. The magnitude of the defects was observed to be concentration-dependent. Moreover, no hatching and spontaneous movement of tail coiling were observed at 400 and 800 μg/mL concentrations due to the delayed growth and early mortality, respectively. A significant reduction in heartbeat rate was also reported for the surviving embryos at the 400 μg/ mL test concentration. The present study has provided preliminary results on the potentially toxic and teratogenic effects of the extract at high concentrations.